Highly Porous Poly(o-Phenylenediamine) Loaded Magnetic Carboxymethyl Cellulose Hybrid Beads for Removal of Two Model Textile Dyes - Arıca, Tuğçe Aybüke; Balcı, Fadime Mert; Balcı, Fadime Mert; Balcı, Sinan; Arıca, Mehmet Yakup; Balcı, Sinan (Springer, 2022)
Ensuring the removal of complex dyes from wastewater is a topic of great interest as it is vital for the environment. The present study reports a facile preparation method for poly(o-phenylenediamine) [p(o-PDA)] micro-particles loaded to magnetic carboxymethyl cellulose (CMC) hydrogel beads as adsorbents. The prepared products were characterized by FTIR, TGA, VSM, SEM, BET, and zeta sizer. The Fe3O4@p(o-PDA)@CMC beads were used for the removal of Reactive Blue 4 (RB-4) and Congo Red (CR) textile dyes from an aqueous medium. Different factors, such as adsorbent dose, initial pH, ionic strength, contact time, temperatures, and initial RB-4 and CR concentrations were examined. The maximum adsorption capacities of the RB-4 dye and CR at optimum pH 5 reached 398.7 and 524.6 mg/g in 120 min, respectively. The adsorption of RB-4 and CR on the hybrid magnetic beads can be due to the electrostatic, hydrogen bonding, and π-π interactions. Moreover, the magnetic hybrid beads showed easy regeneration ability and good reusability. The adsorbent can be a very good candidate for the efficient removal of micro-pollutant from wastewater.
Keywords: Adsorption; Carboxymethyl cellulose; Magnetic